In-hospital parenteral nutrition use: A cohort study of administrative and computational challenges - Marc Romain; Charles Weissman; Khuloud Abu-Tair; Abdallah Alaaldein; Rivki Harari; Orit Bitner; Alexander Furmanov; Shaul Yaari (Clinical Nutrition Open Science)
Summary: Background & aims: Parenteral nutrition is a vital modality administered to patients with gastrointestinal tracts unable to support sufficient nutritional intake. We explored whether administrative and computational challenges encountered when analyzing in-patient parenteral nutrition use are similar to those found when analyzing critically ill patient activities. Methods: A dataset containing 9 years of routinely collected administrative data from a healthcare system comprising tertiary care and community hospitals, was analyzed. Results: Computational and administrative issues found when analyzing in-patient parenteral nutrition data were similar to those found when analyzing critical care data. Some patients had multiple hospital admissions so both the number of individual patients and admissions were quantified. In the tertiary facility 2,984 patients, admitted on 4,121 occasions, received parenteral nutrition for a total of 68,047 days; admission to patient ratio of 1.4. The ratio was 1.2 in the community hospital. Administrative challenges included changes in patient case-mix and medical staff. Computations showed the importance of carefully examining frequency distributions. Age distributions were bimodal, adult body-mass index distributions had Gaussian characteristics and parenteral nutrition administration duration distributions were rightward skewed because some patients received parenteral nutrition for extended periods. Therefore, median rather than mean durations represented central tendency. In the tertiary care institution, mean duration was 17.6 ± 26.1(SD) days but median was 12 days. Conclusion: Parenteral nutrition is administered to heterogenous groups of patients hospitalized in different settings, suffering from various diseases and spanning all ages. Such heterogeneity requires paying attention to data characteristics and administrative issues when examining its in-hospital use.